High Prevalence and Incidence of HIV and HCV Among New Injecting Drug Users With a Large Proportion of Migrants—Is Prevention Failing?. (28th January 2016) - Folch, Cinta; Casabona, Jordi; Espelt, Albert; Majó, Xavier; Meroño, Mercè; Gonzalez, Victoria; Wiessing, Lucas; Colom, Joan; Brugal, M. Teresa; ,
ABSTRACT: Objectives: The aim of this study was to assess differences in the prevalence of HIV and HCV infection and associated risk factors between new (injecting for ≤5 years) and long-term injectors and to estimate HIV/HCV incidence among new injectors. Methods: Cross-sectional study among people who inject drugs (PWID) who attended harm reduction centers in Catalonia in 2010–11. Anonymous questionnaires and oral fluid samples were collected. Poisson regression models were applied to determine the association between HIV/HCV infection and risk factors. Results: Of the 761 participants, 21.4% were new injectors. New injectors were younger than long-term injectors (mean age = 31.6 vs. 37.8) and were more likely to be immigrants (59.0% vs. 33.4%). HIV and HCV prevalence was 20.6% and 59.4% among new injectors, and estimated HIV and HCV incidence 8.7 and 25.1 /100 person-years, respectively. Among new injectors, HIV infection was associated with homelessness (PR = 3.10) and reporting a previous sexually transmitted infection (PR = 1.79). Reporting front/backloading (PR = 1.33) and daily injection (PR = 1.35) were risk-factors for HCV infection. For long-term injectors, HIV risk factors were: having shared syringes (PR = 1.85), having injected cocaine (PR = 1.38), reporting front/backloading (PR = 1.30) and ever having been in prison (PR = 2.03). Conclusion: A large proportion of PWID in Catalonia are new injectors, a subgroup with a high level of both sexual and parenteral exposure and a high incidence rate of HIV/ HCV infections. It is important to improve early diagnosis of these infections among this group, in particular among migrants. To identify and address risk factors for homelessness PWID should be a priority.